From Coffee to Communion: Regenerative Tourism and Spiritual Ethics in Flores, Indonesia - Rudy PRAMONO; Yoseph D. Timba; Juliana (LPPM Universitas Bina Sarana Informatika, 2025)
This study explores the role of local spirituality in shaping regenerative coffee tourism in Flores, Indonesia. Using a qualitative descriptive approach based on semi-structured interviews, participatory observation, and documentation of rituals, the research examines how spiritual values—such as sacred relationships with the land, ancestral offerings, and communal rituals—inform ecologically responsible and culturally rooted tourism practices. The findings reveal that community-based coffee tourism in Flores fosters not only environmental sustainability but also spiritual healing for both hosts and visitors. Framed as a “liturgy of encounter,” tourism becomes a transformative space for reflection, cultural dialogue, and ethical regeneration. This study contributes to the emerging literature on regenerative and spiritual tourism by offering an integrative framework that connects ecology, faith, and community. It also recommends policy support for culturally embedded tourism models that honor local wisdom and spiritual ethics.